2000
DOI: 10.3354/dao043211
|View full text |Cite
|
Sign up to set email alerts
|

A new strain of Cryptocaryon irritans from the cultured olive flounder Paralichthys olivaceus

Abstract: An obligate parasite, Cryptocaryon irritans, which is responsible for the white spot disease of marine fish is known to develop in the temperature regime over 19°C. Recently, however, we found white spot disease of olive flounder Paralichthys olivaceus during winter at water temperatures ranging between 12 and 16°C in Korea. In the present study we isolated a C. irritans-like ciliate from the affected fish and investigated its reproductive characters to compare the newly found ciliate with typical C. irritans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…In the skin of the host grouper fingerling, the trophonts did not penetrate the scale layer and were encapsulated by the outermost single layer of epithelial cells; this increases the development success of the trophonts and the virulence of the parasite, since invasion by theronts and eventual establishment of trophonts can occur with relative ease. Production of daughter tomonts by budding was reported by Jee et al (2000). In the present study, we observed that the presence of tomonts with constrictions and apparent 'budding' did not result in the formation of a new cyst wall and complete separation despite the division of cells inside the cyst.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In the skin of the host grouper fingerling, the trophonts did not penetrate the scale layer and were encapsulated by the outermost single layer of epithelial cells; this increases the development success of the trophonts and the virulence of the parasite, since invasion by theronts and eventual establishment of trophonts can occur with relative ease. Production of daughter tomonts by budding was reported by Jee et al (2000). In the present study, we observed that the presence of tomonts with constrictions and apparent 'budding' did not result in the formation of a new cyst wall and complete separation despite the division of cells inside the cyst.…”
Section: Discussionsupporting
confidence: 58%
“…These were pathological results of the infection. The parasites settle within narrow epithelial enclaves, in extended tunnels burrowed in the epithelium, or in the basement membrane of the gill filament (Diamant et al 1991, Colorni & Burgess 1997, Jee et al 2000. In the present study, some trophonts were observed to have burrowed at the base of the secondary lamella layer (thereby 'lifting' this) and in the branchial arch.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The development of the tomont is affected by temperature (Wilkie and Gordin, 1969), dissolved oxygen, and salinity (Yoshinaga, 2001;Coloni, 1985;Cheung et al, 1979). Strain-specific differences in the periods required for the release of theronts have also been reported (Diggles and Adlard, 1997;Jee et al, 2000). To clarify how environmental factors affect the development of tomont and the periods required for the release of theront may allow the prediction and prevention of outbreaks of cryptocaryoniasis in aquaculture facilities, such as marine net cages and land-based tanks.…”
Section: Discussionmentioning
confidence: 99%